Soil Improvement Using Waste Marble Dust for Sustainable Development - Abdul Waheed; Muhammad Usman Arshid; Raja Abubakar Khalid; Syed Shujaa Safdar Gardezi (Civil Engineering Journal, 2021)
The soils which show very high shear strength in a dry state but rapidly lose their strength on wetting are known as collapsible soils. Such rapid and massive loss of strength produces severe distress leading to extensive cracking and differential settlements, instability of building foundations, and even collapse of structures built on these soils. Waste marble dust is an industrial byproduct and is being produced in large quantities globally poses an environmental hazard. Therefore, it is of the utmost need to look for some sustainable solution for its disposal. The present study focused on the mitigation of the collapse potential of CL-ML soil through a physio-chemical process. The soil is sensitive to wetting, warranting its stabilization. Waste marble dust (WMD) in varying percentages was used as an admixture. The study's optimization process showed that geotechnical parameters of collapsible soil improved substantially by adding waste marble dust. Plasticity was reduced while Unconfined Compressive Strength (UCS) significantly increased while swelling was reduced to an acceptable limit. The California Bearing Ratio (CBR) also exhibits considerable improvement. This study appraises the safe disposal of hazardous waste safely and turns these into suitable material for engineering purposes. Doi: 10.28991/cej-2021-03091746 Full Text: PDF